Finite Element Analysis of Lateral Torsional Buckling Behaviour of Tapered Steel Section with Perforation - Naaim, Nurfarhah; De’nan, Fatimah; Choong, Kok Keong; Azar, Faiz (EDP Sciences, 2016)
This paper presents the finite element analysis of lateral torsional buckling of tapered steel section with perforation. The numerical analysis consists of four main models with a ratio of tapering 0.3 for 3.5m and 5.5m span and ratio of tapering 0.5 for 3.5m and 5.5m span. This study has 94 models in order to investigate the effect of thickness and the openings on the buckling moment. LUSAS software was used to carry out the finite element analysis to study the effect of web opening on the buckling behavior which had five variables such as thickness of web and flange, opening size, ratio of tapering, and opening arrangement. The opening size from 0.2D to 0.4D is recommended because buckling moment capacity difference only around 2% was observed for the opening size exceeds 0.4D. Ratio of tapering 0.3 and ratio of tapering 0.5 was observed increase with the web opening area. The deformation patterns are almost similar for the different sizes of web openings and ratio of tapering. Based on the finite element results, tapered steel section without perforation has higher buckling moment capacity. The comparison of the buckling moment between non-perforated sections with the recommended section is around 2% to 4%.